BUSINESS MARKETING MANAGEMENT SYSTEM (BMMS) - Mohd Razali, Ahmad Farid (Universiti Teknologi PETRONAS, 2020)
Evolvement of technology around the world nowadays had changed a lot of routines around the world. This situation may automate some activities that usually done manually by the people in the past times as there were less of innovation done by the people. The growth of technology helped the people, especially on business purpose to perform their daily process. From all parts of business process, we may explore that some innovations had been done to help the business continuity. This project focusing on one major segment of business, which is marketing. This project aims to assist marketing activities by developing a system which consist of database that records all information of marketing performances and user-friendly dashboard that shows the user all data that is being extracted from the database into some visualisations for analytic purposes. The database will record data from all marketing campaigns from different channels that has been run by the company. This system may help business person to compare all marketing campaigns that has been performed, especially on daily basis.